PENGARUH KEBOCORAN RADIATOR PADA MAIN TRANSFORMER TERHADAP KINERJA OPERASI PEMBANGKITAN LISTRIK: STUDI KASUS PLTA AMPELGADING MALANG - Affansyah, Thaariq; Setiawidayat, Sabar; Siswanto, Diky; Mukhsim, Mohammad (JASEE Journal of Application and Science on Electrical Engineering, 2025)
This study aims to analyze the impact of radiator leakage in the main transformer on the power generation performance at the Ampelgading Hydroelectric Power Plant, Malang. Radiator leakage reduces the volume of insulating oil, leading to increased operating temperatures and degradation of insulation quality. A quantitative descriptive method with a case study approach was employed by analyzing temperature data, Breakdown Voltage (BDV), Dissolved Gas Analysis (DGA), and energy production data before and after the disturbance. The results indicate that radiator leakage caused a significant increase in winding and oil temperatures, along with a decline in insulation oil quality marked by elevated dissolved gas levels. Operationally, the disturbance resulted in a power output reduction of 18.27%. Corrective actions, including cold welding, load reduction, and oil purification, were effective in restoring transformer performance, as evidenced by an average BDV value of 68.1 kV categorized as very good, and improved energy production after maintenance. This study concludes that the reliability of the transformer cooling system, particularly the radiator, plays a crucial role in maintaining operational stability and efficiency in hydroelectric power generation.